Measurements by x-ray diﬀraction of the temperature dependence of lattice parameter and crystallite size for isostatically‑pressed graphite - Hallam, K; Darnbrough, J; Paraskevoulakos, C; Heard, P; Marrow, T; Flewitt, P (Elsevier, 2021)
Synthetic polygranular graphites of various grades and manufacturing routes are used in nuclear reactors for power generation, and may be used in potential fourth generation and other advanced reactor designs that will operate at higher temperature. Attention is given in this paper to isostatically-moulded synthetic polygranular graphites with porosities in the range 8% to 18%. The lattice parameters a and c for the hexagonal graphite have been measured over the temperature range from room temperature to 800°C by x-ray diffraction. The variation with temperature of the crystal lattice parameters, coherence length (crystallite size) and microstrain are discussed with reference to the microstructure and the relative strength of the bonds in-plane and normal to the graphene layers.